THE IMPLEMENTATION OF INDUSTRIAL WORK CULTURE IN VOCATIONAL EDUCATION AS AN EFFORT TO ENHANCE PRACTICAL COMPETENCE AND STUDENT READINESS TO ENTER THE INDUSTRIAL WORLD : SYSTEMATIC LITERATURE REVIEW - Safitri, Feby Salma Ayu; Saputra, Sapta Utama Heru; Diyu, Achmad Ghoni Ken (Journal of Industrial Engineering Management, 2025)
Technical and Vocational Education and Training (TVET) plays a role in preparing a competent and adaptive workforce in the era of globalization. However, the graduates produced have not fully met the qualifications of the workforce as required by the industrial world, therefore one of the strategies in order to improve the quality of graduates is to instill an industrial work culture in the education process to improve their skills so as to increase their competitiveness. This study aims to systematically examine the application of industrial work culture in vocational education as a strategy to improve practical competence and readiness of students to enter the world of work. Through a systematic literature review approach, this study examines both national and international literature relevant to the integration of industrial work culture values with the Vocational High School (SMK) environment. Based on the results of the literature review, industrial work culture has several elements such as the application of 5R/5S (Ringkas, Rapi, Resik, Rawat and Rajin), discipline, responsibility, cooperation (teamwork) can make a positive contribution to strengthening students' character and technical skills. In addition, internship programs also provide contextualized learning experiences that strengthen graduates' work readiness. These findings emphasize the importance of collaboration between educational institutions, industry, and policy makers in designing learning strategies based on industrial work culture to produce vocational graduates who are adaptive and competent amid the dynamic needs of the global industry.